Third record of Rhodnius amazonicus and comparative study with R. pictipes (Hemiptera, Reduviidae, Triatominae) - da Rosa, João Aristeu [UNESP]; Souza, Eder Santos [UNESP]; da Costa Teixeira, Adelson; Barbosa, Rosenildo Ribeiro; de Souza, Aecildo José; Belintani, Tiago; Nascimento, Juliana Damieli; Gil-Santana, Hélcio Reinaldo; de Oliveira, Jader [UNESP] (Elsevier, 2017)
Rhodnius amazonicus Almeida et al. (1973) is a triatomine of rare occurrence. This species was found for the third time in Breves city, Pará state, Brazil. Morphometric and morphological studies were carried out on one male and one female. Lent and Wygodzinsky (1979) considered this species as a synonym of R. pictipes, until its revalidation after 23 years by Bérenger and Pluot-Sigwalt (2002). Considering the synonym mentioned above, a comparative study between these two species was performed in order to report the third encounter of this species, and increase the number of morphological characters that distinguish R. amazonicus from R. pictipes. The dorsal side of the head, the dorsal and ventral portions of the thorax, the dorsal, ventral and posterior sides of the female genitalia, eggs and the median process of the pygophore were examined by scanning electronic microscopy (SEM). The head, thorax, abdomen and egg parameters of these two species were also measured. The identification of characters on the head, stridulatory sulcus, mesosternum, metasternum, scutellum, process of urotergite I, external female genitalia, pygophore and eggs made the distinction between R. amazonicus and R. pictipes possible. This study has shown the new characters recorded and described for the first time for R. amazonicus and R. pictipes by SEM here made it possible to confirm the morphological separation between these two species. The morphometric analysis also confirmed that the above two taxa are different at specific level.
Keywords: Identification; Measurement; Rhodnius amazonicus; Rhodnius pictipes; Scanning